Socioeconomic Characteristics Influencing Level of Awareness of Aflatoxin Contamination of Feeds among Livestock Farmers in Meru District of Tanzania - E. M. Ayo; A. Matemu; G. H. Laswai; M. E. Kimanya (Scientifica)
Aflatoxins occurrence in feeds challenges human and animal health. Farmers’ awareness status of these toxins has an effect on their level of exposure. The study assessed the influence of socioeconomic characteristics of farmers on their awareness of aflatoxin contamination of feeds. Data were collected from 258 households and analysed by SPSS program for descriptive statistics and association between socioeconomic characteristics and awareness of aflatoxin contamination of feeds. Over seventy percent of the farmers had never heard about aflatoxins. Education level, specialization, and period of keeping animals had significant influence on aflatoxin awareness. Hearing about aflatoxins was six times higher among farmers who studied life or social sciences than those without specialization and those who studied other fields. Awareness that aflatoxins may occur in feeds was twice higher among farmers with higher education than those with lower education. Perception that aflatoxins in feeds are detoxifiable was threefold higher among young people (with ≤10-year period of keeping animals) than among older ones. Awareness of aflatoxins was particularly low among farmers with low education and those without exposure to life or social sciences and vice versa. Sensitization is recommended to raise farmers’ awareness on aflatoxin contamination of feeds and incorporating aflatoxin knowledge in school curricula.